Cerebral blood flow abnormalities in children with Sydenham's chorea: A SPECT study - Kabakus, Nimet; Balci, Tansel Ansal; Kurt, Abdullah; Kurt, Aysegul Nese Citak (My University, 2006)
Functional imaging studies in patients with Sydenham's chorea have suggested brain perfusional abnormalities. In this study, we aimed to investigate the cerebral perfusion patterns of the cortical/subcortical structures by using Tc-99m hexamethylpropylenamine oxime single photon emission computed tomography in children with Sydenham's chorea, accompanied with magnetic resonance imaging and cranial Doppler studies. Brain MRI and Doppler studies of the all cases were normal. In the brain SPECT study, six patients were determined to have cerebral perfusion abnormalities. Although six patients responded well to the therapy, two girls who had hypoperfusion in the right frontal region as well as hypo-/ hyperperfusion in the basal ganglia did not respond to therapy. While the chorea form of the patients who have cerebral perfusional abnormality was generalized, the clinical picture of the patients with normal cerebral perfusion was in the form of hemichorea.
Keywords: Brain SPECT; Sydenham's chorea; Tc-99m HMPAO